Organizational intelligence and knowledge analytics - McBreen, Brian; Silson, John; Bedford, Denise (Working methods for knowledge management., 2022)
Over the past century, intelligence has evolved as a practice in several distinct domains. In each domain, it is a unique set of tactics grown out of day to day practices. Its practice has been limited to functional units in large, well-funded enterprises. However, in the knowledge economy, every organization must behave intelligently. The relationship between knowledge and intelligence is a logical one, but it is not one that has been highlighted in either knowledge management or intelligence analysis. Organizational Intelligence and Knowledge Analytics expands the traditional intelligence life cycle to a new framework - Design-Analyze-Automate-Accelerate - and clearly lays out the alignments between knowledge capital and intelligence strategies. Explaining what it means to build intelligence capacity across the organization, this book also includes a toolkit of references to analytical methods. This book is intended for business managers, intelligence professionals, data scientists, competitive and strategic intelligence professionals, and researchers in change management.